2008
DOI: 10.1042/bj20080965
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine-181 is crucial in the enzymatic activity and substrate specificity of human endoplasmic-reticulum aminopeptidase-1

Abstract: ERAP-1 (endoplasmic-reticulum aminopeptidase-1) is a multifunctional enzyme with roles in the regulation of blood pressure, angiogenesis and the presentation of antigens to MHC class I molecules. Whereas the enzyme shows restricted specificity toward synthetic substrates, its substrate specificity toward natural peptides is rather broad. Because of the pathophysiological significance of ERAP-1, it is important to elucidate the molecular basis of its enzymatic action. In the present study we used site-directed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 33 publications
1
29
0
4
Order By: Relevance
“…Though our modeling is tentative and the specific interactions may depend on the nature of a certain substrate, such a model would explain substrate binding in case of a disordered active site. Such a mechanism would also explain the marginal cleavage of shorter peptides, although it has been shown that ERAP1 is able to hydrolyse synthetic substrates (25), albeit with greatly reduced affinity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though our modeling is tentative and the specific interactions may depend on the nature of a certain substrate, such a model would explain substrate binding in case of a disordered active site. Such a mechanism would also explain the marginal cleavage of shorter peptides, although it has been shown that ERAP1 is able to hydrolyse synthetic substrates (25), albeit with greatly reduced affinity.…”
Section: Resultsmentioning
confidence: 99%
“…The pocket is further bordered by the side chain of Met 319 , the aliphatic part of Glu 183 and the carboxamide group of Gln 181 . A previous study showed that mutating Gln 181 to glutamate increased the affinity of ERAP1 for basic N-terminal residues (25). The end of the pocket is formed by the aliphatic part of the side chain of Arg 430 and its bottom is sealed via an electrostatic interaction of the guanidinium group of Arg 430 with the carboxylate of Glu 865 of domain IV, which stacks against the imidazole ring of His 160 from domain I.…”
Section: Resultsmentioning
confidence: 99%
“…Although wild-type enzyme caused a 1.4-fold increase in the activity, enhancement was marginal when RAW264.7 cells were treated with enzymatically inactive E354Q ERAP1, the Zn 2ϩ binding site of which was disrupted. In addition, Q181D ERAP1, which showed different substrate specificity from the wild-type enzyme and cleaved basic amino acids preferentially, also had only a marginal effect (16); thus, the enzymatic activity of wild-type ERAP1 is required for the enhancement of phagocytosis. We then examined the effects of other M1 aminopeptidases, such as placental leucine aminopeptidase (P-LAP)/insulin-regulated aminopeptidase/oxytocinase, laeverin/aminopeptidase Q (APQ), and aminopeptidase A (APA), on the uptake of IgG-coated latex beads (17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
“…Although bestatin inhibited the aminopeptidase activities of wild-type and H379F LVRN/APQ rather efficiently, H379G, H379K, and H379L LVRN/APQs were less susceptible to the inhibitor, suggesting that an aromatic ring of His 379 is important for the bestatin sensitivity of wild-type LVRN/APQ. On the other hand, amastatin inhibited the aminopeptidase activity of H379G LVRN/APQ (K i ϭ 17.3 Ϯ 5.4 M) more effectively than adipocyte-derived leucine aminopeptidase/endoplasmic reticulum aminopeptidase-1 (K i ϭ 41.8 Ϯ 10.3 M), to which amastatin is much more effective than bestatin (24). These results indicated that His 379 was responsible for the unique inhibitor profile of wild-type LVRN/APQ.…”
Section: Hismentioning
confidence: 60%